Nanomaterials: Pros and Contras - Karel Klouda; Hana Kubatova; Eva Zemanova (Communications - Scientific letters of the University of Zilina, 2011)
In its first part the contribution presents basic characteristics of nanoparticles, their history, reason of their different behavior, classification of nanoparticles into natural, man-made and engineered nanoparticles. The article highlights potential risks of nanoparticles and the observation of the precautionary principle in contact with them. There is a special risk present in nanoparticles in the form of aerosols. Inhalation of aerosols consisting of nanoparticles leads to their deposition in the respiratory tract and due to their size they are expected to be further transported in the organism.The contribution presents and discusses results of pilot experiments with the use of modern measuring devices, specifically determination of the quantity and distribution of nanoparticles in the air in an underground carriage during the regular operation, in a city transportation bus, in the working environment of an office building, during fires and their extinguishing, effects of the type of Diesel engine, lighting up of entertainment pyrotechnics and during welding. The last part of the contribution presents experiments demonstrating utilization of some properties of nanoparticles of C60 carbon – fullerene.